1995
DOI: 10.1007/bf02285209
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pancreatitis caused by an autoimmune abnormality

Abstract: Several authors have reported a case of chronic pancreatitis associated with Sjögren's syndrome in which an autoimmune mechanism may have been involved in the etiology and in which steroid therapy was effective. We recently encountered a patient with pancreatitis who had hyperglobulinemia, was autoantibody-positive, and responded to steroid therapy. This patient, however, failed to show any evidence of association with Sjögren's syndrome or other collagen diseases. Although the concept of autoimmune hepatitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
240
0
14

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,284 publications
(258 citation statements)
references
References 22 publications
4
240
0
14
Order By: Relevance
“…We previously demonstrated induction of acinar cell apoptosis, with infiltration of CD8 and CD4 T cells and tacrolimus, an immunosuppressant, attenuates this apoptosis and chronic inflammation in this model (Hashimoto et al, 2000;Yamada et al, 2001). Clinical investigations have demonstrated that infiltration of CD4 and CD8 T cells and high expression of major histocompatibility complex class I and class II antigens by pancreatic epithelial cells is observed in human chronic pancreatitis, suggesting that cell-mediated autoimmune mechanisms are at work (Anderson et al, 1988;Bedossa et al, 1990;Jalleh et al, 1993;Yoshida et al, 1995). Furthermore, autoimmune chronic pancreatitis has been recognized as a new entity in humans defined in terms of lymphocyte infiltration, autoantibody production, and effectiveness of steroid administration (Okazaki et al, 2000).…”
Section: Discussionmentioning
confidence: 73%
“…We previously demonstrated induction of acinar cell apoptosis, with infiltration of CD8 and CD4 T cells and tacrolimus, an immunosuppressant, attenuates this apoptosis and chronic inflammation in this model (Hashimoto et al, 2000;Yamada et al, 2001). Clinical investigations have demonstrated that infiltration of CD4 and CD8 T cells and high expression of major histocompatibility complex class I and class II antigens by pancreatic epithelial cells is observed in human chronic pancreatitis, suggesting that cell-mediated autoimmune mechanisms are at work (Anderson et al, 1988;Bedossa et al, 1990;Jalleh et al, 1993;Yoshida et al, 1995). Furthermore, autoimmune chronic pancreatitis has been recognized as a new entity in humans defined in terms of lymphocyte infiltration, autoantibody production, and effectiveness of steroid administration (Okazaki et al, 2000).…”
Section: Discussionmentioning
confidence: 73%
“…In 1992, Toki et al (9) reported the presence of diffuse irregular narrowing of the main pancreatic duct (MPD) on endoscopic retrograde pancreatography (ERP) in a patient with an unusual type of chronic pancreatitis. In 1995, Yoshida et al (10) proposed referring to the disease in these individuals as "autoimmune pancreatitis" (AIP). The findings in these patients include high serum gamma globulin or immunoglobulin G (IgG) levels, positivity for the presence of antinuclear antibodies (ANA), diffuse enlargement of the pancreas, and response to steroid therapy.…”
Section: Introductionmentioning
confidence: 99%
“…This notion received no further attention in Japan until the mid 90's when Yoshida et al published a case of a patient with chronic pancreatitis and impaired exocrine function with associated autoimmunity [2]. The term AIP was first used here.…”
Section: Introductionmentioning
confidence: 99%